Indigenas de Pantoja - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó el retrato de un grupo de seis homnres indigenas de diferentes etnias al parecer son curacas o jefes.
ENGLISH: A portrait of a group of six indigenous men of different ethnicities was observed, apparently they are curacas or chiefs.

SPANISH: Se observó el retrato de un grupo de seis homnres indigenas de diferentes etnias al parecer son curacas o jefes.
ENGLISH: A portrait of a group of six indigenous men of different ethnicities was observed, apparently they are curacas or chiefs.
Indigenous people of Pantoja
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Chiefs and Authorities.|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Curacas y Autoridades.|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Chiefs and Authorities.